2023
DOI: 10.3390/pharmaceutics15061679
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiofilm Effects of Antimony Tin Oxide Nanoparticles against Polymicrobial Biofilms of Uropathogenic Escherichia coli and Staphylococcus aureus

Abstract: Biofilms are responsible for persistent or recurring microbial infections. Polymicrobial biofilms are prevalent in environmental and medical niches. Dual-species biofilms formed by Gram-negative uropathogenic Escherichia coli (UPEC) and Gram-positive Staphylococcus aureus are commonly found in urinary tract infection sites. Metal oxide nanoparticles (NPs) are widely studied for their antimicrobial and antibiofilm properties. We hypothesized that antimony-doped tin (IV) oxide (ATO) NPs, which contain a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Soleimani and Habibi-Pirkoohi (2017) results showed that silver nanoparticles fabricated from Chlorella vulgaris inhibit the expression of the hla gene even with a concentration less than the MIC. Nanoparticles synthesized from material other than silver nitrate also showed antibacterial activity, nanoparticles from Antimony Tin Oxide (ATONPs) reduce the expression of the hla gene and prevented hemolysin production (Park et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Soleimani and Habibi-Pirkoohi (2017) results showed that silver nanoparticles fabricated from Chlorella vulgaris inhibit the expression of the hla gene even with a concentration less than the MIC. Nanoparticles synthesized from material other than silver nitrate also showed antibacterial activity, nanoparticles from Antimony Tin Oxide (ATONPs) reduce the expression of the hla gene and prevented hemolysin production (Park et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…diclofenac had an effect inactivating the E coli biofilm metabolism the authors observed a biofilm killing activity only when diclofenac was associated with kanamycin or tetracycline, ciprofloxacin (Leão et al, 2020). (Shah et al, 2016) The many traits of biofilms facilitate antimicrobial resistance (Park, 2023). In particular, creating an extracellular polymeric substance (EPS) matrix lessens the diffusion and penetration of antimicrobial drugs while shielding the bacteria from environmental stresses like dehydration and starvation (Espigares et al, 2023).…”
Section: Discussionmentioning
confidence: 99%